-15-5m=-6m+6m

Simple and best practice solution for -15-5m=-6m+6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15-5m=-6m+6m equation:


Simplifying
-15 + -5m = -6m + 6m

Combine like terms: -6m + 6m = 0
-15 + -5m = 0

Solving
-15 + -5m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -5m = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -5m = 0 + 15
-5m = 0 + 15

Combine like terms: 0 + 15 = 15
-5m = 15

Divide each side by '-5'.
m = -3

Simplifying
m = -3

See similar equations:

| 2-5y=5(1-2y) | | 5a+2(a-3)=15 | | 8x^2+10-72=0 | | 4x-8x-8=-3x+4-4 | | -4(4x+6)=16 | | p+6.5p=54 | | 3y-5=-23 | | -3n+6n=3 | | -1/3x+9=-x+3 | | (x/4)+(4/5)=(5/12) | | X^2-6X+9/2x-6 | | 1.15p=46 | | -7z+6z=6z-8-4z | | 9x+9=10x-4 | | 11=6x-3+x | | 7/6a=14 | | 85=2(-5b+2) | | 2x+11=5x-1 | | y-2x=2x-5 | | 3/12=4/x | | 6=-8x+2x | | 3r^2-20r-7= | | 9x+4=6x+7 | | 17x-3=13x-15 | | 5-2(x-1)=11 | | 5.7=-0.6 | | 5(x+2)+38=-3x | | 2p+5q+3p+q= | | w+2/3=2w+1/5 | | v^2-13v+40=0 | | .7(x+60)+.5x=78 | | 8y+2(-1/4-2y)=3/2 |

Equations solver categories